A review of practical approach in suspected infanticide deaths - Tan, Lii Jye; Ong, Beng Beng; Rahim, Nur Syahrina; Koh, Cai Ping; Othman, Mohammad Shafie; Koo, Zhao Peng; Lai, Shau Kong (Elsevier, 2025)
Determining stillbirth or livebirth in cases of infant abandonment is a complex and challenging task in autopsy practice. This distinction is crucial in determining whether the death is link to natural causes or potentially involves criminal implications. This review critically examines current methodologies in postmortem investigations of newborn deaths, emphasizing the importance of accurately distinguishing between stillbirth and livebirth. Our goal is to provide a thorough checklist for forensic practitioners by analyzing pathological, radiological, and biochemical parameters in suspected infanticide investigations. Enhancing the accuracy of these investigations not only aids the judicial process but also serves as a deterrent against newborn abandonment or infanticide. Ultimately, the implementation of stringent legal measures against newborn abandonment is expected to reduce the incidence of infanticide and improve neonatal survival rates.